Hulun Buir: the ethnic and linguistic situation - Khabtagaeva (Adam Mickiewicz University in Poznań, 2019)
Modern Hulun Buir is one of the distinctly multi-ethnic areas in China. It is in many ways comparable to other pronouncedly multi-ethnic regions of northern China. In the following text we present preliminary findings from collective fieldwork in the western part of modern Hulun Buir, which was carried out by the three authors in September 2017. This fieldwork was focused on gathering material for comparative linguistic research and data on the current sociolinguistic situation of the Mongolic (Buryat, Bargu, Daur and Khamnigan Mongol) and Tungusic (Solon, Khamnigan Ewenki languages spoken in western Hulun Buir. The aim of this field report is, first, to describe the current situation of the state of preservation, prestige, and speakers, attitude to the languages under investigation, and, second, to outline the main tendencies and dynamics in the co-existence, contacts, and hierarchy of these languages.